Diplomasi Bencana Alam sebagai Saran Meningkatkan Kerjasama Internasional - Herningtyas, Ratih; Surwandono, Surwandono (Universitas Muhammadiyah Yogyakarta, 2015)
This paper aims to examine how the issue of disasters in Indonesia can be modified into a positive social capital to solve social, economic, political and social culture’s problems in disaster prone areas. Indonesia is very vulnerable to natural disasters. Some of the latest and most destructive natural disasters are the earthquake followed by tsunami that hit Aceh Indonesia on 2004, earthquake hit Yogyakarta and Central Java earthquake on 2006 and volcanic eruption of Mount Merapi Yogyakarta and Central Java 2011. Using qualitative approach, this paper found that Indonesia’s disaster managements get worldwide recognition and increases Indonesia’s competitiveness toward other countries. These recognitions become the sources of Indonesia’s soft power, and can be used as a strategic instrument to build international cooperation and collaboration.